2009
DOI: 10.1095/biolreprod.108.075341
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Induction of Cell Proliferation in the Adult Female Ungulate Brain (Ovis aries) Associated with Activation of the Reproductive Axis by Exposure to Unfamiliar Males1

Abstract: In many species, the reproductive centers of the brain are profoundly affected by sociosexual stimuli. This is particularly evident in female ungulates such as sheep, in which exposure to males switches them from reproductively quiescent to fertile. In two experiments with female sheep, we tested whether the brain centers that control gonadotropin-releasing hormone (GnRH) neuronal activity respond differentially to ''novel'' vs. familiar males and whether the neuroendocrine response is associated with increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 38 publications
(61 reference statements)
3
54
1
Order By: Relevance
“…This was borne out by studies in mice showing that male pheromones that help females to distinguish between subordinate and dominant males induce neurogenesis in the dentate gyrus of the hippocampus, a brain region fundamentally associated with memory (61). We also found that the acute LH response of ewes to novel rams is associated with a rapid (within 2 h) and robust increase in the rate of cell proliferation in the dentate gyrus of the hippocampus (14). Importantly, the odour of the newborn lamb induces cell division in the same region of the brain, indicating that neurogenesis is involved in both cases of the formation of olfactory memory (62).…”
Section: How Do Females Determine Who Is 'Novel' and Who Is 'Familiar'?mentioning
confidence: 61%
See 2 more Smart Citations
“…This was borne out by studies in mice showing that male pheromones that help females to distinguish between subordinate and dominant males induce neurogenesis in the dentate gyrus of the hippocampus, a brain region fundamentally associated with memory (61). We also found that the acute LH response of ewes to novel rams is associated with a rapid (within 2 h) and robust increase in the rate of cell proliferation in the dentate gyrus of the hippocampus (14). Importantly, the odour of the newborn lamb induces cell division in the same region of the brain, indicating that neurogenesis is involved in both cases of the formation of olfactory memory (62).…”
Section: How Do Females Determine Who Is 'Novel' and Who Is 'Familiar'?mentioning
confidence: 61%
“…These observations were mirrored in goats when Véliz et al (11) showed that maintenance of does with bucks did not reduce the proportion of does that ovulated in response to novel bucks. In a recent study, we directly measured the neuroendocrine response of females to novel males and showed that exposure to novel rams increased tonic secretion of LH and induced an LH surge in all ewes (13,14). Importantly, this series of neuroendocrine events did not occur in ewes reexposed to familiar rams after only 15 min of separation ( Figure 2).…”
Section: Novelty Of the Male Stimulusmentioning
confidence: 92%
See 1 more Smart Citation
“…One study did not identify any BrdU þ cells in the hypothalamus of sheep despite detecting BrdU þ cells in the SGZ and using higher intraperitoneal (i.p.) doses of BrdU (Hawken et al 2009). The reason for this discrepancy remains unclear.…”
Section: Adult Neurogenesis In the Hypothalamus: Parenchymal Or Germimentioning
confidence: 99%
“…In sheep, cell proliferation, evaluated by bromodeoxyuridine (BrdU) incorporation, has been observed in the dentate gyrus of the hippocampus of ewes exposed to a novel male (Hawken et al 2009). Using BrdU incorporation and cellular biomarkers such as doublecortin or glial fibrillary acid protein (for review Sierra et al 2011), it has been demonstrated that cell proliferation is down-regulated in the subventricular zone, the dentate gyrus and the main olfactory bulb at parturition and during interactions with the young (Brus et al 2010, Fig.…”
Section: Neurogenesis Cell Proliferationmentioning
confidence: 99%